The Effectiveness of the Intervention Depression in the Elderly: A Systematic Review - Sinaga, Mei Rianita Elfrida (Universitas Muhammadiyah Semarang, 2020)
The increasing life expectancy in Indonesia has an impact on the amount of attention on the elderly population. Depression is becoming one of the health problems of elderly people in the world. This research approach using systematic review aims to gain a greater understanding about the effectiveness of interventions against depression in the elderly. Methods a systematic review was conducted by searching the literature related to the theme taken, namely “intervention”, “depression”, “elderly”. Literature search using Scient Direct, PubMed, and Google Scholar, from the years 2017-2020, so that the obtained 18 articles eligible. Article quality was evaluated using the CASP checklist The results of the articles obtained came from several countries including Indonesia. These interventions can be grouped into three categories, the first physical therapy/exercise, psychological therapies, and spiritual therapies to lower the level of depression in the elderly in a variety of settings such as in nursing homes, in correctional institutions, and the general community, including home visits, using an individual approach or group. This review helped inform some of the interventions that can be performed on the elderly, it can save the cost, feasible and easy to do, and effective to reduce the level of depression in the elderly, and can improve the quality of life, overcome other psychological problems.